2017
DOI: 10.1002/pbc.26561
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain and supplemental O2: Risk factors during the hematopoietic cell transplant admission in pediatric patients

Abstract: Percent weight gain and need for supplemental oxygen is highly associated with the development of respiratory failure in pediatric HCT recipients, representing predictors of acute respiratory failure in pediatric HCT. These data could be incorporated into an algorithm that should be developed, implemented, and validated in a prospective, multicenter fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The Center for International Blood and Marrow Transplant Research reported that between 2008 and 2014, 4408 children aged 18 years underwent a first allogeneic HCT and an additional 3076 received a first autologous transplant [38]. Accepting a 25% incidence of PARDS among pediatric HCT patients [7], there are less than 2000 available patients to be studied over a comparable time period. Consequently, identifying a sufficient number of patients for study requires a large number of centers, each of which is only likely to enroll a handful of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Center for International Blood and Marrow Transplant Research reported that between 2008 and 2014, 4408 children aged 18 years underwent a first allogeneic HCT and an additional 3076 received a first autologous transplant [38]. Accepting a 25% incidence of PARDS among pediatric HCT patients [7], there are less than 2000 available patients to be studied over a comparable time period. Consequently, identifying a sufficient number of patients for study requires a large number of centers, each of which is only likely to enroll a handful of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The recently convened Pediatric Acute Lung Injury Consensus Conference [1,2], along with others [3][4][5][6][7][8], has highlighted differences in outcomes from pediatric acute respiratory distress syndrome (PARDS) in children with immunosuppressive diseases compared with those with a functional immune system. Historically, acute lung injury in these children has been associated with worse survival, particularly among the hematopoietic cell transplantation (HCT) population, with mortality rates of up to 60% [7][8][9][10][11][12][13]. Historically, these children have been excluded from interventional trials evaluating therapeutic interventions for respiratory failure [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 There are limited data regarding the relationship between positive fluid balance and outcome in the pediatric HSCT population, particularly at the point in time when patients become critically ill and warrant care in the PICU. Some have identified !10% weight gain as an independent risk factor for PICU admission, 5 while others noted percentage weight gain is associated with respiratory failure, 11 and there is extremely high mortality associated with >20% increase in fluid balance over the course of the PICU admission. 12 Similarly, others have noted maintaining a negative fluid balance is associated with survival.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid overload status can be assessed by percent weight change. Increased percent weight change is associated with increased mortality and places these patients at higher odds for respiratory failure (19, 20). Given this information this study aimed to assess the validity of Bedside PEWS scoring systems to identify those patients at need of critical care intervention during their transplant admission, and to determine if a modified version of the Bedside PEWS that includes weight as a variable is more predictive of the need for PICU admission or is more highly associated with increased mortality in this select patient population.…”
Section: Introductionmentioning
confidence: 99%